Effects of Ketamine and Xylazine on the Neurological and Cardiorespiratory Variables in Puppies Born by Caesarean Section (Journal of Hama University, 2022)
The research was done on twelve non breed pregnant bitches weighing( 16-25) k.g Aging ( 2-5) years . which entered  par partration and all of them have undergone Caesarean section in the veterinary teatching hospital of the Faculty of Veterinary Medicine in  Hama university . The bitches was divided into two groups. The first group was given a dose of (ketamine  5.5 m.g/ k.g) in addition to (xylazine 1 m.g / k.g ) intramuscularly ; while The control  group had bitches which had pregnancy period and gave birth normally .There were 28 puppies in the first group while the Control Group had 25 puppies . The puppies, heart and respiratory rates and their pain reflex, sucking, and flexion reflexes were measured as they were removed from the uterus and after one, two ,and 24 hours .The results showed significant  differences on average in the first group compared with the study group.The neurological reflexes also showed significant differences between the Control Group and the study group .In conclusion ,The (ketamine - xylazine ) group showed decreasing in heart rate ,breathing and neurological  reflexses compered with the control  group at p